Metabolite characterization of Neptunia oleracea Lour. and its correlation with antioxidant and alpha-glucosidase inhibitory activities using NMR-based metabolomics approach - Lee, Soo Yee (2017)
Diabetes mellitus is a metabolic disease characterized by high blood glucose levels. Due to the unpleasant side effects of currently available synthetic drugs, traditional medicinal plants have drawn the attention of researchers who are seeking natural compounds for the control of diabetes. This present study focused on the profiling and characterization of metabolites in local medicinal plants with potential antioxidant and α-glucosidase inhibitory activities. The first part of the study assessed the total phenolic contents (TPC), DPPH free radical scavenging and α-glucosidase inhibitory activities of 5 local medicinal plants. Of these plants, Neptunia oleracea exhibited the highest TPC and most potent DPPH free radical scavenging and α-glucosidase inhibitory activities. Subsequently, the second part of the study examined the influence of different drying methods on metabolite variations among N. oleracea leaves and stems using an NMR-based metabolomics approach. The results showed that freeze drying was the most suitable drying method for preserving the metabolites in N. oleracea; whereas the N. oleracea leaves possessed higher TPC and better bioactivities than its stems. Multivariate data analysis (MVDA) revealed that the identified phenolics, including catechin, caffeic and gallic acids and derivatives of apigenin, quercetin, kaempferol and myricetin were responsible for the discrimination and potent bioactivities of freeze-dried N. oleracea leaves. Then, the third part of the study focused on an investigation of the relationship between these phenolics and the tested bioactivities. The effects of different extraction methods and ethanol ratios were also investigated. Both partial least square (PLS) and random forests (RF) analysis identified caffeic acid and derivatives of apigenin, quercetin and kaempferol as the most effective DPPH scavengers and α-glucosidase inhibitors of N. oleracea. To extract these phenolics, sonication with absolute ethanol was the most suitable extraction condition. Consequently, in the next part of the study, the freeze-dried N. oleracea leaf extracts obtained via sonication with absolute ethanol were fractionated using solid phase extraction (SPE) to obtain hexane (HF), chloroform (CF), ethyl acetate (EF) and methanol (MF) fractions. Of these fractions, EF and MF displayed the most significant bioactivities, and were then subjected to UPLC-MS/MS analysis, which resulted in the identification of 37 metabolites, with mostly phenolics. Through various chromatographic techniques, 5 phenolics including quercetin-3-O-β-D-xylopyranoside (28), quercetin-3-O-α-Larabinopyranoside (30), quercetin-3-O-α-L-rhamnoside (32), methylgallate (11) and rutin (22) were isolated from these fractions. Individual testing of the bioactivities of these phenolics showed that methylgallate (11) exhibited the most potent DPPH scavenging and α-glucosidase inhibitory activities, with the IC50 values of 17.25 and 50.76 μM, respectively. In summary, this study suggested that N. oleracea is a prominent source of phenolics which can be potential antioxidant and α-glucosidase inhibitors for the management of diabetes. This study is the first report on the antidiabetic potentiality of N. oleracea, and the first application of metabolomics approach for extensive study of the phytoconstituents and their correlation with antioxidant and α-glucosidase inhibitory activities of this plant. The results of this study lay the foundation for future research regarding the antidiabetic effect of N. oleracea.